ANALISIS KOMPARATIF PENGUNGKAPAN KATEGORI LINGKUNGAN LAPORAN KEBERLANJUTAN (Studi Kasus pada PT Pupuk Kalimantan Timur dan PT Petrokimia Gresik) - Elsa Enda Dwita Purba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to analyze the sustainability reports of PT Pupuk Kalimantan Timur and PT Petrokimia Gresik, especially in terms of their conformity with the prevailing standards of GRI-G4. GRI-G4 has three indicators for the disclosure of sustainability report category: economic, environment, and social. This research focuses on environment disclosure for the sake of assessing the companies’ responsibility towards the environment as both of the fertilizer companies use natural resources as their main ingredients for production activities. The analysis assesses the two companies’ activities and reports eith regard to the standard GRI-G4. The results of the research indicate that PT Pupuk Kalimantan Timur has conducted its environmental duties and responsibilities for at least 76%; meanwhile, PT Petrokimia Gresik has been performing its tasks and responsibilities to the environment for at least 61 % of the environmental category of GRI-G4.The research indicates that the sustainability reports of PT Pupuk Kalimantan Timur meet the standard of GRI-G4 in the category of environment more that those of PT Petrokimia Gresik.Keywords: Sustainability Report, Disclosure, Environmental Category, PT Pupuk Kalimantan Timur, PT Petrokimia Gresik, GRI-G4